2023
DOI: 10.1186/s13018-023-03981-5
|View full text |Cite
|
Sign up to set email alerts
|

The development, incidence and treatment trends of trochanteric fractures in Germany: a cohort study

Abstract: Background Hip fractures are a major public health problem worldwide and can lead to disability, increased mortality, and reduced quality of life. We aim to provide a nationwide epidemiological analysis of trochanteric and subtrochanteric fractures and their respective surgical treatments. Methods Data were retrieved from the national database of the German Department of the Interior. ICD-10-GM and OPS data from the period of 2006 to 2020 were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The risk of performing revision surgery even after immobilization failure is about 3.5 times higher than that of PFNA [9,19].IMN technology continues to evolve and mature, and the era of DHS as a monopoly seems to be a thing of the past. In Germany and Ireland, for example, research teams in both countries analyzed the surgical methods performed by patients with intertrochanteric fractures in their countries, and the results showed that the most popular internal xation system was the IMN, while the frequency of DHS use was declining [24,25]. So, what are the advantages of IMNs over DHS?…”
Section: Extramedullary Versus Intramedullarymentioning
confidence: 99%
“…The risk of performing revision surgery even after immobilization failure is about 3.5 times higher than that of PFNA [9,19].IMN technology continues to evolve and mature, and the era of DHS as a monopoly seems to be a thing of the past. In Germany and Ireland, for example, research teams in both countries analyzed the surgical methods performed by patients with intertrochanteric fractures in their countries, and the results showed that the most popular internal xation system was the IMN, while the frequency of DHS use was declining [24,25]. So, what are the advantages of IMNs over DHS?…”
Section: Extramedullary Versus Intramedullarymentioning
confidence: 99%